2022
DOI: 10.1177/1071181322661082
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Preferences for Lower-Limb Prosthesis: A Think-Aloud Study during User-Guided Auto-Tuning

Abstract: Prostheses help amputees to maintain physical health and quality of life. Prosthesis wearers’ satisfaction and adherence to the prosthesis are closely related to the preferences for prosthesis tuning settings. However, the underlying factors that contribute to the preferences were under-explored. In this study, two able-bodied participants were asked to change the robotic prosthesis settings to their preferred state and the think-aloud technique with a mixed-method approach was used to reveal the contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Consistent with previous studies that found large inter- individual differences in preferences for degrees of ankle stiffness (e.g., Shepherd et al, 2020), we also found high variability in their preferences for not only the magnitude, direction, and pattern of the changes but also the underlying reasoning or factors related to naturalness (Schaffalitzky et al, 2009). Among the factors, the workload sub-theme was not mentioned in the non-disabled participants (Yuan et al, 2022a), surprisingly, nor in two amputee participants. Although it was only mentioned by one amputee participant, it doesn’t mean that the other participants did not have the experience or the need.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Consistent with previous studies that found large inter- individual differences in preferences for degrees of ankle stiffness (e.g., Shepherd et al, 2020), we also found high variability in their preferences for not only the magnitude, direction, and pattern of the changes but also the underlying reasoning or factors related to naturalness (Schaffalitzky et al, 2009). Among the factors, the workload sub-theme was not mentioned in the non-disabled participants (Yuan et al, 2022a), surprisingly, nor in two amputee participants. Although it was only mentioned by one amputee participant, it doesn’t mean that the other participants did not have the experience or the need.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to Yuan et al (2022a), we employed a mixed method approach, with the qualitative method (i.e., the think- aloud technique) as the main focus, supplemented with quantitative ratings on preference levels and other experiences. The main goal was to follow the amputees’ natural preferences and reveal the underlying reasons as they make changes to the prosthesis pretending that this is the device they would use in daily life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the profile exploration trials for this study have been performed sequentially and there was no way for participants to assess how changing one control point changes their perception of the others. Thus, our ongoing study aims to analyze the psychological aspects that can drive prosthesis users' choices during the extensive exploration of their preferences while also considering the interdependent relationships between control points that could affect profile perception [43].…”
Section: B Preferred Profile Analysis and User Preferencementioning
confidence: 99%